2017
DOI: 10.18869/acadpub.ibj.21.1.32
|View full text |Cite
|
Sign up to set email alerts
|

In silico Screening and Evaluation of the Anticonvulsant Activity of Docosahexaenoic Acid-Like Molecules in Experimental Models of Seizures

Abstract: Background: Resistance to antiepileptic drugs and the intolerability in 20-30% of the patients raises demand for developing new drugs with improved efficacy and safety. Acceptable anticonvulsant activity, good tolerability, and inexpensiveness of docosahexaenoic acid (DHA) make it as a good candidate for designing and development of the new anticonvulsant medications. Methods: Ten DHA-based molecules were screened based on in silico screening of DHA-like molecules by root-mean-square deviation of atomic positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…AdCA also showed sedative effect; the anti-seizure effect of AdCA appeared at the sedative doses. This finding is in line with our previous study in which the non-sedative doses of AdCA did not show anticonvulsant activity in PTZ and MES models [2] . Results of our study showed that the margin between sedative and anticonvulsant doses of AdCA was narrow in the PTZ model as PI value of 0.87 was obtained for AdCA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…AdCA also showed sedative effect; the anti-seizure effect of AdCA appeared at the sedative doses. This finding is in line with our previous study in which the non-sedative doses of AdCA did not show anticonvulsant activity in PTZ and MES models [2] . Results of our study showed that the margin between sedative and anticonvulsant doses of AdCA was narrow in the PTZ model as PI value of 0.87 was obtained for AdCA.…”
Section: Discussionsupporting
confidence: 93%
“…Using bioinformatics tools and pharmacophore drug design, we have previously introduced several compounds with potential anticonvulsant activity [2] . Though all candidate molecules had adequate safety, a few compounds were effective in experimental seizure models [2] . One of the candidate molecules was AdCA (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods suggest changing a chemical structure of known AEDs or phenotypic screening of compounds with unknown mechanisms [7,8]. In silico methods are the useful tools, which help to predict biological activity and structure of designed compounds [11]. Moreover, these tools are able to notice phenotypic and genotypic differences between AEDs in polytherapy [12].…”
Section: Introductionmentioning
confidence: 99%